Gender integration in agricultural policies: Uncovering strengths, gaps, and implications for gender equality and rural women’s empowerment - Acosta, Mariola; Osorio, Martha; Stloukal, Libor; Valverde, Ivanna; Vilimelis López, Silvia; Phillips, Lauren M. (Food and Agriculture Organization of the United Nations, 2023)
The last decade has seen growing commitment to tackling gender inequalities in agriculture. The formulation of gender-responsive agricultural policies is central for ensuring that the vision, priorities, and implementation strategies that are set nationally for the sector take due account of the genderdifferentiated needs and constraints of men and women. The objective of this study is to examine the extent and manner in which agricultural-related policies integrate gender equality and rural women’s empowerment concerns, and to identify strengths and gaps in policy-formulation processes. The study applies the Gender in Agricultural Policies Analysis tool (GAPo) to assess 83 main agricultural policies of low, lower-middle, and upper-middle-income economies. 94 BOOK OF ABSTRACTS Our results show that although 17% of the reviewed agricultural policies fail to recognize and address gender inequality within the sector, most policies integrate gender consideration to some extent. At the same time, our analysis reveals notable gaps in policy formulation. These gaps include a limited ambition of the proposed gender interventions, a lack of women’s meaningful participation in policy development, and inadequate recognition of discriminatory social norms. Furthermore, important challenges such as genderbased violence and climate change receive insufficient consideration. We discuss the importance of these gaps and suggest measures to ensure more genderresponsive policy-making, to improve the lives and well-being of women engaged in agriculture.